2021
DOI: 10.3390/jcm10040807
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Statin Therapy and Long-Term Recurrence of Atrial Fibrillation after Cardioversion: A Propensity-Matched Analysis

Abstract: The relationship of statin therapy with recurrence of atrial fibrillation (AF) after cardioversion (CV) has been evaluated by several investigations, which provided conflicting results and particularly long-term data is scarce. We sought to examine whether upstream statin therapy is associated with long-term recurrence of AF after CV. This was a single-center registry study including consecutive AF patients (n = 454) undergoing CV. Cox regression models were performed to estimate AF recurrence comparing patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Given the role of redox status in AF, statins may be helpful in the reduction in AF recurrence rates after successful cardioversion. A new single-centre registry study from 2021, including 454 patients, showed that statin therapy resulted in an absolute risk reduction of 27.5% for recurrent AF after cardioversion [ 83 ]. The study took into account the pleiotropic effect of statins, likely resulting in a decreased OS and anti-inflammatory effect.…”
Section: Antioxidants In Arrhythmia Treatmentmentioning
confidence: 99%
“…Given the role of redox status in AF, statins may be helpful in the reduction in AF recurrence rates after successful cardioversion. A new single-centre registry study from 2021, including 454 patients, showed that statin therapy resulted in an absolute risk reduction of 27.5% for recurrent AF after cardioversion [ 83 ]. The study took into account the pleiotropic effect of statins, likely resulting in a decreased OS and anti-inflammatory effect.…”
Section: Antioxidants In Arrhythmia Treatmentmentioning
confidence: 99%